23. THE WORKING MOTIVATION OF MEDICAL STAFF AND SOME RELATED FACTORS AT HOSPITAL OF TRADITIONAL MEDICINE X, 2023 (Vietnam Journal of Community Medicine, 2023)
Background: Work motivation is an internal factor that stimulates people to work hard in conditions that allow to create high-quality and effective productivity [9]. Health human resources are a very important component of the health system. ensuring the efficiency and quality of health services, directly affecting people’s satisfaction. Good management and administration of health human resources not only helps improve the quality of health services but also enhances equity in health care and improves the efficiency of human resource use [7]. Objective: Describe the working motivation of medical staff at X Traditional Medicine Hospital and analyze some related factors. Methods: Cross-sectional description, with analysis, tools using self-completed questionnaires. Results: An analysis of 401 medical staff at X Traditional Medicine Hospital showed that the work motivation of medical staff achieved an overall average score of 3.73/5 points with the rate reaching the level of motivation. motivation is 74.6% and the percentage of medical staff with high motivation is 47.4%, low motivation is 52.6%. Factors related to high motivation of health workers include: leadership group (OR=2.23; 95%CI:1.01- 4.93) and health workers with 20 years of service experience or more (OR=7 .85; 95%CI: 1.65-37.40) Conclusion:The rate of highly motivated employees is 47.4%, the rate of employees with low motivation is 52.6%, Factors related to work motivation: age group, type of labor, intensification. Working years, the group is satisfied with the working conditions, the group is satisfied with the relationship conditions of superiors and colleagues, and is satisfied with the management regime and policies.
Keywords: Work motivation, medical staff, related factors.